The use of yoga as a therapeutic method in people with autistic spectrum disorder: An integrative review - Viana, Maria Laiane dos Santos (2021)
Objectives: To characterize scientific productions considering the variables: journal, type of study, databases, year of publication and study contributions and to identify how the use of yoga as a therapeutic method in people with autism spectrum disorder is being addressed in the scientific literature. Methodology: This is an integrative literature review study. The collection took place in August 2020, in the PubMed databases via Medline, Web of Science, Scopus, Latin American Literature, LILACS, BDENF and SciELO. The search terms were selected from the consultation with Health Sciences Descriptors (Decs), "Yoga", "Artistic disorder" and "autism spectrum disorder", as well as the uncontrolled terms autism and childhood autism. Articles published in Portuguese, English and Spanish from 2009 to 2019 were made available in full. Result: The twelve articles that met the proposed inclusion criteria, the manuscripts were published in the years 2010 and 2019, highlighting the year 2019 (33%). Regarding the origin of the articles, six (50%) publications are from the USA, five (42%) in India, one (8%) in Iran. Regarding the database, one Web of Science stood out with nine (75%) scientific productions. Conclusion: It is concluded that the use of yoga as treatment in accordance with autism spectrum disorder is still a subject that requires studies in many countries. In addition, the practice of yoga in people with autism spectrum disorder contributed in a way to decrease personal and social well-being.